Understanding and strengthening the health of family businesses in Laos - Walsh, John (Information Management and Business Review, 2011)
More than 90% are family-businesses and are concentrated in retail, handicrafts, and personal services sectors. More than half are female-owned and managed, although baseline information about business and family management are limited. This paper reports on qualitative research aimed at understanding family business practices, impact of education in family businesses in a range of activities in Laos. Most such businesses remain based at or very close to home, and along the main road with any growth managed by hiring additional family members. Firms were run on traditional lines, while the management decisions were generally taken by senior family members depending on their existing prejudices. Although family businesses in Laos are still largely disorganized, they play critical roles in creating job opportunities and boosting household income for local residents as well as helping family members to utilize their existing talents, time, and resources. In promoting this sector, the Government of Laos has significant roles in developing policies, establishing a relevant governing agency, and encouraging training and involvement from the private sectors and from key international organisations.